Potential of Freshwater Microalgae in Biodegradation of Disposable Face Masks - Deviany, Deviany; Nainggolan, Gabriela; Br Pelawi, Luluinaita (Journal of Chemical Process Engineering, 2024)
The use of disposable face masks can reduce the transmission of Covid-19 through saliva splashes from infected patients. However, the use of these masks causes waste generation that has the potential to release microplastic fibers into the environment. Biodegradation by freshwater microalgae can be a solution to handling disposable face mask waste. Microalgae were isolated from retention ponds in Institut Teknologi Sumatera using Walne fertilizer and pineapple liquid waste (LCN) as alternative growth media. Selected isolate was used to degrade three-ply mask pieces with Walne:LCN media ratios of 1:0,; 0:1, and 1:1 as well as Walne media without the addition of isolate as a control. Analysis of the masks degradation results was carried out using gravimetric and Fourier Transform Infraredmethods. Gravimetric analysis showed a decrease in mask mass after degradation for the control, 1:0, 0:1, 1:1 treatments, which were 0.0004grams, 0.0054grams, 0.0088grams and 0.0193grams, respectively. FTIR analysis showed new functional groups (O-H), increased C=C, and decreased C-H % transmittance of the masks after degradation. It can be concluded from the analysis that microalgae isolated from ITERA’s retention basin was able to degrade disposable masks, which is characterized by a decrease in mask mass and changes in % transmittance of C=C and C-H functional groups. The addition of LCN did not show a significant effect on mask degradation compared to variations without LCN, as evidenced by the FTIR results in the 1:1 variation where no alkene groups appeared and the alkyl group spectrum peaks were not much different from the control